Cerebral blood volume lesion extent predicts functional outcome in patients with vertebral and basilar artery occlusion. Issue 5 (July 2019) - Alemseged, Fana; Shah, Darshan G; Bivard, Andrew; Kleinig, Timothy J; Yassi, Nawaf; Diomedi, Marina; Di Giuliano, Francesca; Sharma, Gagan; Drew, Roy; Yan, Bernard; Dowling, Richard J; Bush, Steven; et al.
Background: CT perfusion may improve diagnostic accuracy in posterior circulation stroke. The posterior circulation Acute Stroke Prognosis Early CT score (pc-ASPECTS) on Computed Tomography Angiography source images (CTA-SI) predicts functional outcome in patients with basilar artery occlusion. Aims: We assessed the prognostic value of pc-ASPECTS on CT perfusion in patients with vertebral and basilar artery occlusion (VBAO) in comparison with CTA-SI. Methods: Whole-brain CT perfusion from consecutive stroke patients with VBAO at four stroke centers was retrospectively analyzed. pc-ASPECTS – a 10-point score assessing hypoattenuation on CTA-SI – was calculated from CT perfusion parameters as focally reduced cerebral blood flow or cerebral blood volume, focally increased time to peak of the deconvolved tissue residue function (Tmax) or mean transit time. Two investigators independently reviewed the images. Reliability was assessed with intraclass correlation coefficient. Good outcome was defined as modified Rankin scale ≤3 at three months. Results: We included 60 patients with VBAO. After assessment of four CT perfusion maps simultaneously, area-under-ROC curve (AROC) was 0.83 (95%CI 0.72–0.93) for cerebral blood volume, 0.76 (95%CI 0.64–0.89) for cerebral blood flow, 0.77 (95%CI 0.64–0.89) for Tmax, 0.70 (95%CI 0.56–0.84) for mean transit time versus area-under-ROC curve 0.64 (95%CI 0.50–0.79) for CTA-SI. Cerebral blood volume had greater accuracy compared with CTA-SI for poor outcome (p = 0.04). In logistic regression analysis, cerebral blood volume pc-ASPECTS≤8 was independently associated with poor outcome (OR 9.3 95%CI 2.2–41; p = 0.003, adjusted for age and clinical severity). Inter-rater agreement was substantial for cerebral blood volume pc-ASPECTS (intraclass correlation coefficient 0.82 95%CI 0.71–0.90 versus 0.67 for CTA-SI 95%CI 0.43–0.81). Conclusions: Cerebral blood volume pc-ASPECTS may identify VBAO patients at higher risk of disability.